Thinking Narratively Between Novel-Essay and Narrative Essay - Fusillo, Massimo; Simonetti, Gianluigi; Marchese, Lorenzo (Transcodification: Arts, Languages and Media, 2022)
What is the connection between philosophical enquiries and storytelling in contemporary narrative? Is it possible to outline some features of a so-called philosophical fiction in Western literature throughout the last two centuries? This book aims to provide a plural answer, hosting extensive essays by seven young researchers coming from different fields (Theory of literature, German, American, Russian and Italian contemporary literature, history and evolution of the essayistic form). A short The volume is addressed to all those with a strong interest in both evolution of philosophical speech and history of the novel and has a strong vocation to promote interdisciplinarity in literary studies.